Analysis of non-retinopathy of prematurity (ROP)–related fundus hemorrhage in preterm infants in China - Yaoyao, Sun; Kaixin, Deng; Xiaoxin, Li; Min, Zhao; Yanrong, Jiang; Hong, Yin; Huijun, Qi; Tong, Qian; Dandan, Linghu; Wenzhen, Yu; Mingwei, Zhao; Jianhong, Liang (Frontiers in Pediatrics, 2022)
Objective: To determine the incidence of fundus hemorrhage (FH) not associated with retinopathy of prematurity (ROP) during ocular screening and report their clinical features, risk factors, therapies, and prognosis in a large population of premature newborns. Methods: The medical records of all preterm newborns admitted to the Department of Ophthalmology, Peking University People’s Hospital, Beijing, from January 1, 2016 through August 31, 2021 were retrospectively reviewed. Fundus examinations were carried out by experienced retinal experts. Examination under anesthesia was carried out in newborns with abnormal fundus including vitreous hemorrhage (VH) or retinal hemorrhage (RH) >2 discs’ diameter by a Retcam2 system. A lens-preserving vitrectomy was performed in infants requiring a vitrectomy. A comprehensive medical history was also recorded and analyzed. Result: During the 5-year period, a total of 7,260 preterm babies were screened. There were 82 (1.13%) newborns and 104 (0.72) eyes with FH, including VH or RH. Twelve (14.63%) newborns (16 eyes, 15.38%) had VH; 56 (68.29%) (74 eyes, 71.15%) had flame-shaped, superficial hemorrhages; six (7.31%) (6 eyes, 5.77%) had small, round, deep hemorrhages (<2 disk diameters in size); and eight (9.76%) (8 eyes, 7.69%) had large, round hemorrhages (>2 disk diameters). In all, there were 10 (12.20%) cases of intracranial hemorrhage. The mode of delivery was not found to be a significant factor in the occurrence of birth-related retinal hemorrhage (P=0.22). Six newborns (eyes) with large, round retinal hemorrhage at the posterior pole while the macular was not impacted and 11 cases (15 eyes) with vitreous hemorrhage were required to receive close follow-up with average follow-up time of 105 days. A lens-sparing vitreous surgery was conducted in three patients without any complications. Conclusion: Preterm newborns with FH that are not caused by ROP are more likely to have superficial, peripheral hemorrhages,. Vaginal delivery compression and forceps may be associated with hemorrhage. A lens-preserving vitrectomy is required and considered safe for dense FH involving the refractive media.